Association Between Chlamydia trachomatis and Helicobacter pylori with Inflammation in Polycystic Ovary Syndrome: A Cross-Sectional Study - Yeşim Alpay Çağlar; Mine Islimye Taşkin (Medicina)
Objective: Chronic low-grade inflammation occurs in polycystic ovary syndrome (PCOS), and there are many contributing factors. In this study, we aimed to investigate Helicobacter pylori and Chlamydia trachomatis infections in patients with PCOS and to evaluate the association between these microorganisms and the inflammatory process in the etiology of the disease. Materials and Methods: This comparative cross-sectional clinical study was conducted at Balıkesir University Hospital and included 40 female patients diagnosed with PCOS in the gynecology outpatients clinic and 40 healthy female controls. Demographic data were recorded. Blood hormone profiles and biochemical parameters were analyzed. An enzyme-linked immunosorbent assay test kit was used to measure H. pylori IgG and C. trachomatis IgG. Results: According to the analysis of the study data, there was no significant association between the PCOS and non-PCOS groups with regard to the presence of Helicobacter pylori IgG (p = 0.1) and Chlamydia trachomatis IgG (p = 0.338). CRP levels were significantly higher in the PCOS group (p = 0.001). In the subgroup analyses, the CRP levels were not significantly different between the H. pylori and C. trachomatis antibody-positive and -negative groups. Diabetes mellitus was significantly associated with PCOS (p = 0.005). The smoking rate was significantly higher in the control group than in the PCOS group (p = 0.036). Compared to the control group, the BMI, LH, HOMA-IR, TSH, and TG levels were significantly higher in participants with PCOS (p = 0.000; p = 0.004; p = 0.001; p = 0.001; p = 0.043; p = 0.000). FSH was lower in PCOS patients compared to controls (p = 001). In the subgroup analyses, no significant differences were found between the H. pylori and C. trachomatis antibody-positive and -negative groups. Conclusions: PCOS is characterized by chronic nonspecific low-grade inflammation. The etiopathogenesis of PCOS involves comorbidities that cause a chronic inflammatory process. However, the possible infective causes still seem to be open to investigation. In particular, studies on microbiota and periodontal diseases in PCOS may provide important contributions.